2017
DOI: 10.18632/oncotarget.19452
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing molecular weight of octyl chitosan as drug carrier for improving tumor therapeutic efficacy

Abstract: Macromolecular drug carriers have attracted much attention taking advantage of passive tumor targeting property and excellent biocompatibility. For many biomedical applications, however, the effectiveness of the carriers is insufficient, which complicate further development into clinical use. Here, we systematically investigated the effects of molecular weight (from 1KDa to 300KDa) of macromolecular drug carrier, octyl chitosan, on tumor accumulation and penetration, as well as drug loading and releasing profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In fact, previous literature indicated that dextran-TAC conjugate was estimated to contain 0.45% of TAC . However, the drug loading in our HA-ADH-TAC conjugate has been increased to 1% approximately, which could be attributed to the low molecular weight of HA used in the study …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, previous literature indicated that dextran-TAC conjugate was estimated to contain 0.45% of TAC . However, the drug loading in our HA-ADH-TAC conjugate has been increased to 1% approximately, which could be attributed to the low molecular weight of HA used in the study …”
Section: Resultsmentioning
confidence: 97%
“…26 However, the drug loading in our HA-ADH-TAC conjugate has been increased to 1% approximately, which could be attributed to the low molecular weight of HA used in the study. 46 3.3. Solubility Studies.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 98%
“…Other groups have shown that molecules of low molecular weight, such as DM1 and MMAE, penetrate compact surfaces at much faster rates than large molecules of high molecular weight (32) (37) (38). For instance, Zhang et al, recently showed that if the molecular weight of the molecular drug carrier, octyl chitosan (OC), is 1kDa, it is able to fully penetrate into spheroids after 8 hours of incubation (39). However, if the molecular weight of OC is of 10kDa, its penetration efficiency drops by over 50% after 8h of incubation.…”
Section: Discussionmentioning
confidence: 99%